(untitled) (Indian Journal of Animal Production and Management, 2024)
Electricity is essential to dairy farming and electrically powered machines are used for milking, automatic feed dispensers and heated water bowls. Leakage of current from these equipments, high voltage lines or faulty connections between the electrical circuit and the earth can lead to an undesirable electrical phenomenon called stray voltage. Stray voltage is a small voltage (<10V) that can be measured between two possible contact points. Cows can sense voltages at approximately one-tenth of a human being. Humans have inherently higher body resistance than cows and generally have shoes or boots while working in barns, which further increases resistance. Consequently, humans do not feel what animals feel. Stray voltages less than 0.5 volts are considered normal. Stray voltages vary, depending on the circuits used and the amount of moisture in the soil around the grounding rod. Impact of stray currents on livestock at current 1 - 3 mA: At current 4 - 6 mA: common behavioral response such as flinching or delaying drinking water. At current > 6 mA (up to 10): Feed intake is reduced, resulting in lower meat and milk production. Common symptoms of stray voltage in cows include hesitation to enter the parlor, they may stampede or rush out of the parlor when released, cows dance or step around constantly while in the milking parlor, Normal milk letdown is interrupted, Increased milking time, Udder irritation caused by residual milk and increased somatic cell count which increases the incidence of mastitis.